Adenoid cystic carcinoma of the breast: Report of two cases with immunohistochemical profile of C-kit and MYB overexpression - Susie Chin; Zisun Kim (Wolters Kluwer Medknow Publications, 2014)
Adenoid cystic carcinoma (ACC) is a rare tumor with characteristic histologic features. Staining with basal markers for estrogen receptor, progesterone receptor, and HER2 usually shows negative results. Immunohistochemical analysis of C-kit and MYB overexpression of the ACC also has been reported. We report two cases of ACC of the breast with C-kit and MYB overexpression that clinically confirm these previously reported characteristics and suggest that further molecular study of the expression of these two proteins can lead to future therapeutic strategies.